Pengaruh Program Bantuan Sosial Keluarga Harapan (PKH)Terhadap Kesejahteraan Masyarakat di Kecamatan Sumber Jambe Kabupaten Jember - Lilia Oktafia; Rafael Purtomo Somaji; Regina Niken Wilantari (UPT Penerbitan Universitas Jember, 2020)
The decrease in the added value of GRDP during the Covid-19 pandemic turned out to be expanding the unemployment rate and eliminating people's opportunities to earn income, loss of learning opportunities and getting proper health services due to the economic limitations of the people of Sumber Jambe District, Jember Regency. GRDP as a benchmark for the economy in a country will show economic performance both regionally and nationally. One of the government's steps in fulfilling the function of fiscal policy is the allocation of the APBD for public welfare which is distributed by the Ministry of Social Affairs in the form of the Family Hope Program (PKH). This study aims to analyze the effect of the Family Hope Program (PKH) on public welfare. To answer the research objectives, the method used is a simple linear regression model with an ordinary least squares (OLS) approach. The results showed that the family hope program had a positive effect on the welfare of the community in Sumber Jambe District.